Analisis Perubahan Kebijakan Luar Negeri Korea Selatan Dalam Pemasangan Sistem Terminal High Altitude Area Defense (THAAD) - Qonita, Maulida Ibnaty; Hanura, Marten (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
A country's foreign policy is the most important thing in the continuity of relations with other countries, but does not leave behind the values that apply in the domestic sphere. Policy makers need to consider domestic interests in order to set the policies. The policy of installing the Terminal High Altitude Area Defense (THAAD) missile system in South Korea was determined in response to a North Korean nuclear test. However, this policy caused various negative reactions from domestic and other countries. Furthermore, negative reactions also comes from other countries such as China for several reasons of their objections. This study aims to determine the factors that cause changes in South Korea's foreign policy in the installation of the Terminal High Altitude Area Defense (THAAD) missile system. This study uses the Upper-left Box Liberalism theory with an actor-centrational rationalist approach. This type of research is qualitative which aims to understand the process of changing a country's foreign policy. The results of the research are domestic interests and international restrains influence a country in establishing its foreign policy. For further research, the authors suggest discussing this case with other views or theories so that they can be seen from various perspectives. Moreover, the discussion of South Korea's policies in the installation of anti-missiles can be seen from the point of view of other countries that the authors are unable to discuss further and more detail.